Public administration : theory and practice - Singh, Hoshiar; Sachdeva, Pardeep (New Delhi : Pearson, 2012)
Building upon the idea that public administration is the most vital tool of governance, and Public Administration: Theory and Practice explores its role in preserving and promoting peace in a welfare state. Written for undergraduate students, the authors lay immense stress on the fundamental theme and the key concepts throughout the discussion in the book to develop students' understanding and discourse skills in the field.
Keywords: Public Administration